2001
DOI: 10.1038/83513
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification and characterization of hammerhead-ribozyme inhibitors using fluorescence-based technology

Abstract: The ability to rapidly identify small molecules that interact with RNA would have significant clinical and research applications. Low-molecular-weight molecules that bind to RNA have the potential to be used as drugs. Therefore, technologies facilitating the rapid and reliable identification of such activities become increasingly important. We have applied a fluorescence-based assay to screen for modulators of hammerhead ribozyme (HHR) catalysis from a small library of antibiotic compounds. Several unknown pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
9

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 39 publications
(49 reference statements)
0
41
0
9
Order By: Relevance
“…RNA contains complex and sophisticated higher order structures that are essential for recognition by other macromolecules and/or required for catalytic processes+ As such, it offers an interesting target for small molecule ligands and, indeed, the ability of RNA to interact with small molecules has long been recognized+ Antibiotics are a chemically and structurally diverse collection of molecules, with some classes capable of interacting with rRNA to exert profound effects on the translation process+ Functional insights from structural studies of compounds bound to ribosomal subunits have revealed that rRNA/small molecule ligand recognition is based on a combination of shape recognition, electrostatic, and hydrogen-bonding interactions Pioletti et al+, 2001;Schlunzen et al+, 2001)+ Additionally, RNA SELEX (Systematic Evolution of Ligands by Exponential Enrichment) has enabled the identification of minimal nucleic acid recognition motifs for ligand binding, demonstrating that RNA three-dimensional structures can form a large number of highly specific ligand-binding sites (Gold et al+, 1995)+ The ribosome is the target for many important antibacterial agents; these compounds interfere with essential steps of protein synthesis (Pestka, 1977;Gale et al+, 1981;Noller, 1991)+ Among these, 2-deoxystreptamine aminoglycosides (small polycationic compounds possessing linked ring systems consisting of aminosugars and an aminocyclitol) cause codon misreading by interfering with the decoding process + These compounds have found clinical use as antibacterial agents due to their ability to specifically bind bacterial ribosomes (Gale et al+, 1981) and are thought to exert their effects by increasing the error rate of the ribosome + Eukary-otic cytoplasmic ribosomes are relatively insensitive to 2-deoxystreptamine aminoglycosides (Kurtz, 1974;Palmer & Wilhelm, 1978;Wilhelm et al+, 1978aWilhelm et al+, , 1978b, and it has been suggested that the sensitivity of a ribosomal system to antibiotics is determined by the sequence of its rRNA (Sor & Fukuhara, 1984;Beckers et al+, 1995)+ Indeed, the nephrotoxicity and ototoxicity associated with use of aminoglycosides in the clinical setting may be linked to the susceptibility of mitochondrial ribosomes to these compounds (Bottger et al+, 2001)+ Aminoglycosides are also capable of binding to and affecting the activity of a large number of other RNAs, including the HIV TAR element (Mei et al+, 1997), HIV Rev-responsive element (Zapp et al+, 1993), hammerhead ribozymes (Stage et al+, 1995;Jenne et al+, 2001), hairpin ribozymes (Earnshaw & Gait, 1998), ribonuclease P RNA …”
Section: Introductionmentioning
confidence: 99%
“…RNA contains complex and sophisticated higher order structures that are essential for recognition by other macromolecules and/or required for catalytic processes+ As such, it offers an interesting target for small molecule ligands and, indeed, the ability of RNA to interact with small molecules has long been recognized+ Antibiotics are a chemically and structurally diverse collection of molecules, with some classes capable of interacting with rRNA to exert profound effects on the translation process+ Functional insights from structural studies of compounds bound to ribosomal subunits have revealed that rRNA/small molecule ligand recognition is based on a combination of shape recognition, electrostatic, and hydrogen-bonding interactions Pioletti et al+, 2001;Schlunzen et al+, 2001)+ Additionally, RNA SELEX (Systematic Evolution of Ligands by Exponential Enrichment) has enabled the identification of minimal nucleic acid recognition motifs for ligand binding, demonstrating that RNA three-dimensional structures can form a large number of highly specific ligand-binding sites (Gold et al+, 1995)+ The ribosome is the target for many important antibacterial agents; these compounds interfere with essential steps of protein synthesis (Pestka, 1977;Gale et al+, 1981;Noller, 1991)+ Among these, 2-deoxystreptamine aminoglycosides (small polycationic compounds possessing linked ring systems consisting of aminosugars and an aminocyclitol) cause codon misreading by interfering with the decoding process + These compounds have found clinical use as antibacterial agents due to their ability to specifically bind bacterial ribosomes (Gale et al+, 1981) and are thought to exert their effects by increasing the error rate of the ribosome + Eukary-otic cytoplasmic ribosomes are relatively insensitive to 2-deoxystreptamine aminoglycosides (Kurtz, 1974;Palmer & Wilhelm, 1978;Wilhelm et al+, 1978aWilhelm et al+, , 1978b, and it has been suggested that the sensitivity of a ribosomal system to antibiotics is determined by the sequence of its rRNA (Sor & Fukuhara, 1984;Beckers et al+, 1995)+ Indeed, the nephrotoxicity and ototoxicity associated with use of aminoglycosides in the clinical setting may be linked to the susceptibility of mitochondrial ribosomes to these compounds (Bottger et al+, 2001)+ Aminoglycosides are also capable of binding to and affecting the activity of a large number of other RNAs, including the HIV TAR element (Mei et al+, 1997), HIV Rev-responsive element (Zapp et al+, 1993), hammerhead ribozymes (Stage et al+, 1995;Jenne et al+, 2001), hairpin ribozymes (Earnshaw & Gait, 1998), ribonuclease P RNA …”
Section: Introductionmentioning
confidence: 99%
“…It is of significant interest that the two most potent inhibitors of ribozyme function in cells that we identified appear to inhibit ribozyme self-cleavage via their covalent incorporation into the mRNA carrying the ribozyme sequences, as evidenced by the inability of these molecules to inhibit ribozyme selfcleavage in vitro and by the loss of self-cleavage activity when these molecules are incorporated. Based on the welldescribed interactionsb etween specific aminoglycosides and other small molecules and RNA (Stage et al 1995;Murray and Arnold 1996;Hermanna nd Westhof 1998;Tor et al1998;Jenne et al 2001), we had expected that our extensive screen of compounds would have led to the identificationo fc ompounds that inhibit ribozyme selfcleavage by virtue of their direct binding to ribozymecontaining RNA. Ourinability to identify such compounds may suggest that the complexs tructure of mRNA molecules and their associated proteins present in mammalian cells greatly restricts the possibilities for the types of interactions between small moleculesa nd RNAs that can lead to the inhibition of RNA self-cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than rely on in vitro screens of compounds, we chose to develop am ammalian cell-based screeni no rder to directly identify molecules capableo f functioning within cells. Since av ariety of aminoglycoside (Stage et al 1995;Murray and Arnold 1996;Hermann and Westhof 1998;Tor et al 1998;Jenne et al 2001) and nonaminoglycoside antibiotics (Jenne et al 2001)h ad been previously shown to be able to inhibit the self-cleavage of hammerhead ribozymes in the in vitro setting, we first screened such compounds in the cell-based assay.W et hen extended the studies to include the high-throughput screening of 58,076compounds. We report here the results of those screening efforts and the characteristics (and in some cases,the mechanism of action) of the inhibitors that were identified.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that aminoglycoside antibiotics inhibit the cleavage reaction of the ribozyme (126). Among various aminoglycosides that have been tested (such as gentamycin, kanamycin, neomycin, paramomycin, lividomycin, ribostamycin, neamine, butirosin, apramycin and streptomycin), neomycin and 5-episisomicin have been reported as the strongest inhibitors (127,128). Neomycin (Fig.…”
Section: Antibioticsmentioning
confidence: 99%
“…1D), tuberactinomycin B (TubB), enviomycin (TubN) and capreomycin. Studies, based on fluorescence technology, have shown that the cyclic pentapeptide compounds TubA and TubB are very strong hammerhead inhibitors (127). This inhibitory effect might be mediated by an OH group that all these inhibitors contain in a-position of the guanidino group in their sixmembered ring.…”
mentioning
confidence: 99%